The Multigenerational Legacy of Diabetes, Emotional Reactions, and Insulin Adherence - Scollan-Koliopoulos, Melissa (Journal of Social Health and Diabetes, 2020)
Purpose The purpose of this study was to estimate the effect of having a multigenerational legacy of diabetes on insulin adherence by measuring memories of family members’ experiences with insulin self-injection.Methods A cross-sectional correlational design was implemented by surveying hospitalized adults with type 2 diabetes who recently transitioned to using insulin. Surveys included items about the vividness, frequency, and controllability of memories of a family member self-injecting insulin and concordant emotional reaction, and one’s own emotional reaction to a diagnosis of diabetes and insulin regimen adherence.Results A diverse sample responded to the surveys. Significant associations were revealed between having a recollection of a family member fearing insulin injections and a negative emotional reaction toward one’s own diabetes diagnosis with suboptimal insulin adherence. Suboptimal insulin adherence may be an indication of avoidance-based coping. Inquiry into how a multigenerational legacy of diabetes influences individual coping styles for diabetes self-management will help clinicians identify patients at risk for suboptimal insulin adherence.
Keywords: diabetes; insulin; self-care; coping; illness perceptions; multigenerational legacy of diabetes